(3TQM GdThGgO GdUZQis - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj GdMfaj,J (B855 (3g` s
(3ChdgG (B:s
(3hHYO, jbhd(B: (3Ef LdI ef GdCPcjGA hNdI ef GdCdHGA hNGWHhG HCf TQM GdThGgO GdPj febJg s
(3BNQgG (B:s
(3hGdhghH eHGdZI hGgH, hGdeLRd ef CLRd EPG CYWi YWGA cKjQkG bGd GdeDda QMeg Gddg(B: (3hgPG BNQ eG GNJUQfGg ef GdThGgO s
(3fSNI QGHYI JJab aj ChdgG hBNQgG eY GdfSNI GdChdis
(3HGNJdGa jSjQ aj HYV GdCdaGXs
(3hJdG BNQgG TQM NWHI ebOeI GdcJGHs
(3aj fMh CQHY hQbGJ s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdfMhs